Paddy-cum-Fish Farming for the Apatani farm families in North-East Region of India - Misra, V K; Pratap, Arvind; Singh, C P; Tripathi, A N (Indian Farming, 2015)
The tribal people in Arunachal Pradesh, belonging to the Apatani Valley have developed an efficient ecosystem which provides them economic self-sufficiency and an agro-ecosystem that is ecologically sound and helpful in conservation of indigenous natural resources.